Konsep Dasar Pengelolaan Kelas dalam Tinjauan Psikologi Manajemen - Salmiah, Maryati; Rusman, ِAbdul Aziz; Abidin, Zainal (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
Improving the quality of education is determined by the implementation of education management standards. An important factor for the success of learning is decided by the teacher's insight into classroom management. Library research is used to find answers to a problem by carrying out some activities to collect, process, and conclude data. Based on the data in this study, it was concluded that the objectives of classroom management: 1) to create conducive classroom situations and conditions, 2) to eliminate obstacles in teaching and learning interactions, 3) to provide and manage learning facilities, 4) to foster and to guide according to individual characteristics. There are three components in classroom management, namely: physical conditions, socio-emotional conditions, and organizational conditions. Actions that need to be taken in managing the class are preventive actions, corrective actions, and curative actions.